DETERMINING FINANCIAL PERFORMANCE: THE EFFECT OF GREEN INTELLECTUAL CAPITAL AND COMPANY SIZE - Go Cecilia Claudia Pratama; Rini Tri Hastuti (Graduate Program of Universitas Tarumanagara, 2026)
This study was mean to examines the extent effect of green intellectual capital and company size on financial performance. The data studied was data on financial sector companies listed on the IDX in the form of annual and sustainability reports for 2022-2024. The sampling technique used was purposive sampling. The research data is panel data processed using application named Eviews 13. Conclusion of the study is that GIC has an insignificant negative effect on financial performance, while company size has a significant negative effect on financial performance. The empirical inconsistency of this study is that some of the results have an effect and some do not. There are also studies with significant and insignificant results. The gap phenomenon that occurs is that global economic fluctuations cause the average ROA to be only 1.8% in the 2023-2024 range due to hidden costs and structural risks. In fact, the costs incurred by companies (some of which are disclosed by companies through sustainability reports) and the government related to sustainability are quite large. There are several differences in research results that mention a positive and negative relationship between the X variables and Y variables.